Bibliometric study of global health research from Indonesia in international journals - Muhammad Fauzan 'Azhima; Gonda Yumitro (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This article analyzes the trend of international publications related to Global Health in Indonesia using the Scopus database based on region, publication subject, publication type, number of documents per author, and number of papers per university. Research methods. The data collected by the researcher was taken from the Scopus database with the keywords “Global Health” and “Indonesia” and included the categories of article titles, article abstracts, and article keywords for the publication period 1999 - 2023. Data analysis. This study used VOSviewer to visualize Global Health trends in Indonesia. Results. This study found 504 documents related to Global Health in Indonesia, with the highest number of publications in 2023 (71 documents, 14.0%). Indonesia became the most productive country with 245 papers (48.6%). Hay and Murray were recorded as the most productive authors with nine articles, while Universitas Indonesia was the institution with the most publications (60 articles). Conclusions. Over the past decade, global health research in Indonesia has grown due to international collaboration, medical science dominance, and strong institutional contributions, particularly from Universitas Indonesia. This study has revealed significant actors, thematic goals, and financing patterns. The findings highlight Indonesia's growing influence on global health discourse and suggest using Web of Science and Google Scholar for future research.